Intra-Christian Violence and the Problematisation of the World Christian Paradigm - Bruner, Jason ca. 20./21. Jh. (The journal of ecclesiastical history, 2023)
Violence is a crucial lens for inquiring historically into Christianity worldwide. The field of World Christianity, however, has been oriented by a paradigm of growth, success and Christian converts’ creative agency. This article establishes the need for a historiographical intervention in the literature on World Christianity through a critical analysis of texts that have formed the field, followed by examinations of anti-Evangelical violence in nineteenth- and twentieth-century Mexico, and Catholic-Protestant conflicts in colonial East Africa. These case studies identify lacunae in the field and suggest that violence has often been a constitutive part of the contextual formation of World Christianity.